Global DNA methylation in a population with aflatoxin B(1) exposure - Wu, Hui-Chen (Landes Bioscience, 2013)
We previously reported that global DNA hypomethylation, measured as Sat2 methylation in white blood cells (WBC), and aflatoxin B(1) (AFB(1)) exposure were associated with increased hepatocellular carcinoma risk. In this study, we assessed the association between AFB(1) exposure and global DNA methylation. We measured LINE-1 and Sat2 methylation in WBC DNA samples from 1140 cancer free participants of the Cancer Screening Program (CSP) cohort. Blood and urine samples were used to determine the level of AFB(1)-albumin (AFB(1)-Alb) adducts and urinary AFB(1) metabolites. In continuous models, we found reverse associations of urinary AFB(1) with LINE-1 and Sat2 methylation. The odds ratio (OR) per 1 unit decrease were 1.12 (95%CI = 1.03–1.22) for LINE-1 and 1.48 (95%CI = 1.10–2.00) for Sat2 methylation. When compared with subjects in the highest quartile of LINE-1, we found that individuals in the 2nd and 3rd quartiles were less likely to have detectable AFB(1)-Alb adducts, with ORs (95%CI) of 0.61 (0.40–0.93), 0.61 (0.40-.94), and 1.09 (0.69–1.72), respectively. The OR for detectable AFB(1)-Alb was 1.81 (95%CI = 1.15–2.85) for subjects in the lowest quartile of Sat2 methylation. The OR for detection of urinary AFB(1) for those with LINE-1 methylation in the lowest quartile compared with those in the highest quartile was 1.87 (95%CI = 1.15–3.04). The corresponding OR was 1.75 (95%CI = 1.08–2.82) for subjects in the lowest quartile of Sat2 methylation. The association between AFB(1) exposure and global DNA methylation may have implications for the epigenetic effect of AFB(1) on hepatocellular carcinoma development and also suggests that changes in DNA methylation may represent an epigenetic biomarker of dietary AFB(1) exposure.